The Influence of Service Attributes on Customer Intention to Revisit Sharia Hotel with Halal Awareness as a Moderating Variable - Anggraeni, Novita; Zaerofi, Afif; Indra, Indra (Review of Islamic Economics and Finance, 2024)
Purpose – This research aims to analyze the effect of service attributes, including halal food and beverages, sharia-compliant hotel facilities, sharia-compliant hotel operations, and Sharia-compliant hotel design, to revisit Sharia hotels in Jakarta, Bogor, Depok, Bekasi (Jabodetabek) areas with halal awareness as a moderating variable.Methodology – The data utilized consisted of 150 respondents who are Muslim consumers who have previously stayed and revisited Sharia hotels in the Jabodetabek area. Sampling technique used was purposive sampling. The data were analyzed using structural equation modeling (SEM) and processed through partial least squares (PLS) analysis.Findings – This research found that Sharia-compliant hotel operations and design significantly and positively influence consumers' intention to revisit Sharia hotels in Jabodetabek. However, halal food and beverages, as well as Sharia-compliant hotel facilities, ddid not have a significant impact on repeat visits. Halal awareness, as a moderating variable, has not been able to strengthen the influence of Sharia hotel service attributes on repeat visits.Keywords: Service Attributes; Repeat Visits; Sharia Hotel; Halal Awareness.